2007
DOI: 10.1016/j.aim.2006.07.020
|View full text |Cite
|
Sign up to set email alerts
|

The core of zero-dimensional monomial ideals

Abstract: The core of an ideal is the intersection of all its reductions. We describe the core of a zero-dimensional monomial ideal I as the largest monomial ideal contained in a general reduction of I . This provides a new interpretation of the core in the monomial case as well as an efficient algorithm for computing it. We relate the core to adjoints and first coefficient ideals, and in dimension two and three we give explicit formulas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
(52 reference statements)
1
25
0
Order By: Relevance
“…This statement is analogous to the characterization of the integral closure I of I as the largest ideal containing I with the same multiplicity e 0 . However, our interest inǏ has also been motivated by a recent connection, made in [18], with the computation of the core of I (we recall that core(I) is the intersection of all the reductions of I). The core of an ideal has lately been under much scrutiny: One of the classical motivations to study the core comes from the Briançon-Skoda theorem, but more recently Hyry and Smith have shown that Kawamata's well-known conjecture on the existence of sections of line bundles is equivalent to a statement about the core of certain ideals in section rings.…”
Section: This Gives a Filtration Of Subalgebrasmentioning
confidence: 99%
“…This statement is analogous to the characterization of the integral closure I of I as the largest ideal containing I with the same multiplicity e 0 . However, our interest inǏ has also been motivated by a recent connection, made in [18], with the computation of the core of I (we recall that core(I) is the intersection of all the reductions of I). The core of an ideal has lately been under much scrutiny: One of the classical motivations to study the core comes from the Briançon-Skoda theorem, but more recently Hyry and Smith have shown that Kawamata's well-known conjecture on the existence of sections of line bundles is equivalent to a statement about the core of certain ideals in section rings.…”
Section: This Gives a Filtration Of Subalgebrasmentioning
confidence: 99%
“…, x n ]], reduces to compute the intersection of all ideals J of O n such that Γ(I) = Γ(J) and J is Newton non-degenerate. We remark that the study of the core of an ideal is quite an active research topic in commutative algebra (see for instance [8] or [12]). …”
Section: ) Is Non-degenerate With Respect To the Non-zero Ideals Of Tmentioning
confidence: 99%
“…We end by saying that the numerical data we explicitly determine also allow us to compute the reduction number of Ferrers ideals, which is a key ingredient in determining the structure of the core of ideals. Indeed, some classes of monomial ideals possess a surprising interpretation for their core (see [44]). Preliminary investigations also show that the core of a Ferrers ideal has a remarkable structure related to the shape of the corresponding Ferrers tableau.…”
Section: Figure 1 Ferrers Graph Tableau and Idealmentioning
confidence: 99%